Methamphetamine-Induced Locomotor Changes are Dependent on Age, Dose and Genotype - Good, Renee L. (2010)
Adolescence is a critical age for addiction formation as a large percentage of pathological drug-seeking behaviors manifest during this time. The extent to which neurotoxic effects of drugs of abuse influence subsequent drug seeking behaviors and impulsivity is an understudied area of research. Methamphetamine (METH) is a widely abused drug that produces locomotor responses ranging from behavioral sensitization to tolerance, both of which are behaviors that may relate to risk of abuse. Here we investigated the effects of age, genotype, METH dose, including a neurotoxic dose, and METH metabolism on open-field activity (OFA) to gain insight into the complex disease of drug abuse. C57Bl/6 (B6), DBA/2 (D2), and 129S6SvEv/Tac (129) mouse strains were administered saline or either a high dose (4 × 5 mg/kg in 2h intervals for 2 days) or low dose (2 × 1 mg/kg in 24h intervals) METH pretreatment during adolescence (post natal day (PND) 40) or early adulthood (PND 80) followed by behavioral testing with a METH (1 mg/kg) or saline challenge 40 days later. Striatal concentrations of METH and AMPH were also determined. Significant findings include: 1) METH pretreated adolescent B6 mice displayed significant sensitization for horizontal locomotion due to high dose METH pretreatment; 2) METH pretreated B6 adults showed significant tolerance for the vertical activity measure caused by low dose METH pretreatment; 3) METH pretreated adult D2 mice exhibited significant sensitization for vertical activity induced by low dose METH pretreatment, and 4) 129 mice metabolized METH significantly faster than the B6 and D2 mice, but METH pretreatment did not alter metabolism. No significant behavioral responses to either METH pretreatment dose were observed for the D2 adolescent studies or either 129 age group. Our results highlight the importance of the interactions of age, strain and METH dose on locomotor behavioral outcomes.